Work-Hardening and Recovery Studies of Pure Aluminium. - Ojediran, Surajudeen Oluwafemi (Obafemi Awolowo University, 2014)
The effects of work-hardening and recovery on the strength of pure aluminium have been investigated. The modes of interaction of these two processes during creep deformation were closely examined. The Bailey-Orowan equation was derived without recourse to a mechanical equation of state. This new method of derivation clearly showed that the Bailey-Orowan equation is applicable only to steady-state but not to transient creep deformation.